Mattering is an indicator of organizational health and employee success. Issue 2 (4th March 2021) - Reece, Andrew; Yaden, David; Kellerman, Gabriella; Robichaux, Alexi; Goldstein, Rebecca; Schwartz, Barry; Seligman, Martin; Baumeister, Roy
ABSTRACT: Mattering, one's sense of the difference one makes in the world, has been variously described in psychological and philosophical literatures. We propose the experience of mattering is tied to the perceived impact of one's actions and is best understood as an action-oriented, context-dependent construct. We introduce the Organizational Mattering Scale (OMS) for measuring mattering in organizations. Across four studies, factor analysis revealed a general mattering factor and two sub-factors, recognition and achievement (CFI = .98, RMSEA = .06). Construct validity and predictive validity are established across a range of psychological and organizational measures. Notably, OMS scores were more related to self-efficacy than self-esteem ( p < .01), and positively related to key business outcomes, including job satisfaction ( r = .51, p < .01), having a leadership role ( t = 6.91, p < .01), recent promotions ( t = 2.26, p < .05) and retention ( r = .31, p < .01).